Strategi Komunikasi Humas BAKTI Komdigi dalam Menanggulangi Pemberitaan Negatif: Pendekatan Media Monitoring Digital - Yusuf, Azahra Yustia; Rahmawati, Yulia; Praptiningsih, Novi Andayani (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study analyzes the media monitoring strategy implemented by the Public Relations Division of BAKTI Komdigi in handling negative news related to internet service. Using a qualitative case study approach, data were collected through interviews, observation, and documentation. The findings reveal that media monitoring is not only a tool for tracking information but also a crucial component of issue management, as outlined by Chase and Jones (1977). It enables PR practitioners to identify issues, analyze media coverage, and develop appropriate communication strategies. BAKTI Komdigi’s PR team applies a selective approach in responding to news, based on media reach and impact on public opinion. These findings affirm that media monitoring is a strategic instrument for fostering institutional communication that is both responsive and adaptive to public information dynamics.